E-Learning as a Means of Knowledge and Learning at Higher Education Level - Maliha Nasir (PJDOL, 2023)
E-learning is a new trend in educational scenario that provides easy access to learning opportunities through internet. Internet not only provides a wide range of information through a large plethora ofwebsites on various fields of life; but also provides opportunity to learn specific courses through Massive Open Online Courses (MOOCs). These courses may be helpful in promoting knowledge and skills